Two new species of the spider Family Zodariidae from Laos - Zhang, Bao-Shi; Zhang, Feng (Zootaxa, 2018)
Two new Zodariidae species, collected from the natural forest of Pakse City, Champasak Province, Laos, are described as Asceua adunca sp. nov. (male, female) and Mallinella renaria sp. nov. (male, female). Asceua torquata (Simon, 1909) and A. piperata Ono, 2004 are newly recorded from Laos, and the male of A. piperata is described and illustrated for the first time.